Clinical Characteristics of Non–Squamous Cell Carcinoma of the Vagina. Issue 2 (February 2015) - Nomura, Hidetaka; Matoda, Maki; Okamoto, Sanshiro; Omatsu, Kohei; Kondo, Eiji; Kato, Kazuyoshi; Umayahara, Kenji; Takeshima, Nobuhiro
<x xml:space="preserve">Abstract</x> Objective The prognosis and vaginal disease control rate after treatment with radiotherapy or concurrent chemoradiotherapy (CCRT) are reported to be worse for primary non–squamous cell carcinoma (non-SCC) of the vagina than for squamous cell carcinoma (SCC) of the vagina. Our objective was to examine the clinicopathological characteristics of primary non-SCC of the vagina and suggest an appropriate treatment strategy. Materials and Methods In a retrospective chart review, we identified patients with primary vaginal cancer who were treated in our hospital between 1990 and 2013. Twelve patients with histologically diagnosed non-SCC were identified. None of these cases was associated with in utero diethylstilbestrol exposure. Clinical data, including patient characteristics, stage, treatment outcome, and the site of recurrence, were recorded. Results The 12 identified cases included 5 of clear cell carcinoma, 3 of adenocarcinoma, 2 of adenosquamous carcinoma, 1 of carcinosarcoma, and 1 of mucinous adenocarcinoma. The most common location of the tumor was the upper one third of the vagina (56%). Initial treatment involved surgery in 8 patients. Among them, 4 received adjuvant chemotherapy, 3 received adjuvant radiotherapy, and 1 received neither. The initial treatment among the remaining 4 patients was CCRT in 1, neoadjuvant chemotherapy in 2 (followed by CCRT or surgery), and best supportive care in 1. The last 3 patients had lung metastasis. Six patients experienced recurrence, including vaginal recurrence in 2 patients and lymphatic spread in 4 patients. Five of these 6 patients experienced hematogenous metastasis. Conclusions Despite the absence of in utero diethylstilbestrol exposure in our cases, clear cell adenocarcinoma accounted for 41.7% (5/12) cases. A favorable local control rate was achieved in all 12 cases, but the incidence of distant metastasis, especially to the lung, was high. Prevention of distant metastasis may be the key to treating patients with non-SCC of the vagina.